1998
DOI: 10.1086/209904
|View full text |Cite
|
Sign up to set email alerts
|

Technological Change and the Skill Acquisition of Young Workers

Abstract: CLG wcjnqrn © uocc !2 AU uoi o xcq wo bi.ibp urn? pc driocq ipont QxbJ!c bcuuI2!ou bLoAqQq ipt nji © T2 P V1U b B'4I uq WCIJIIUJ 2!CPCIU VII LJU L2GLAQq 2p014 2QCI 01J2 O Xt O ECOUOIJJ!C c2cIcp 2nq vu? ob!u!oua cxbLccq 9i.c gJoac 0j JG vcupoi.z uq uo ipo2c o ipc I4tOWfl B'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
93
0
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(100 citation statements)
references
References 0 publications
4
93
0
3
Order By: Relevance
“…Some authors such as Bartel and Sicherman (1998) or Autor et al (1998) distinguish two types of technological changes, depending on the extent to which the new technology complements or substitutes skills acquired through schooling. They find that a positive relationship between human capital and workers' productivity appears when the introduction of a technology complements skills already acquired by workers during their schooling.…”
Section: Technology/knowledge Intensitymentioning
confidence: 99%
“…Some authors such as Bartel and Sicherman (1998) or Autor et al (1998) distinguish two types of technological changes, depending on the extent to which the new technology complements or substitutes skills acquired through schooling. They find that a positive relationship between human capital and workers' productivity appears when the introduction of a technology complements skills already acquired by workers during their schooling.…”
Section: Technology/knowledge Intensitymentioning
confidence: 99%
“…This assumption also relies on findings in previous research. Bartel and Sicherman (1998) use the NLSY79 data from 1987 through 1992 and find that production workers in manufacturing industries with higher rates of technological change are more likely to receive formal company training. Gashi, Pugh and Adnett (2008) reach a similar conclusion using an administrative German dataset.…”
Section: Wage Dynamics and Returns To Cognitive Abilitymentioning
confidence: 99%
“…Many studies have shown that more educated workers have greater potential for learning during employment (e.g. Bartel & Sicherman, 1998). Case studies of US electronics ® rms in Malaysia document their long-term investment in building up the skills of the local workforce (Hobday, 1995).…”
Section: Notesmentioning
confidence: 99%